Amplification, Cloning And Characterization Of Genomic Sequences Coding For Rna Helicase Gene From Aedes Aegypti - Ibrahim, Ahmad H. (2010)
The mosquito Aedes aegypti is an important vector of arbovirus pathogens, such as dengue fever and other diseases. About 2.5 billion people live in regions where transmission of dengue virus occurs. This makes a vital demand to control these diseases and their vectors. Studies on the genomics of living organisms including Aedes aegypti can improve our understanding of the disease vectors and help us to control these diseases. Extensive studies have identified enzymes that are able to unwind complementary strands of a duplex nucleic acid. These enzymes are known as helicases. RNA helicases are proteins involved in several aspects of RNA metabolism, including transcription, pre-mRNA splicing, ribosome biogenesis and cytoplasm transport.